Public and digital memory regarding two female prisons during Francoism - Hernández Holgado, Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this article is to present a mainly descriptive balance of two digital projects dedicated to the memory and history of women incarcerated during Francoism in Spain, the only ones existing with respect to female prisons: the Barcelona prison of Les Corts (1939-1955) and the female prison of Ventas in Madrid (1933-1969). In both cases, historical studies have gone hand in hand with memory, through interviews and testimonials of the inmates and their families, present in the respective digital projects in the form of audios and audiovisual elements. Besides, in both cases, there is social participation through amanuensis associations, neighborhood collectives, and relatives of the inmates which has played a decisive role in a slow-moving social task against forgetfulness.